2014
DOI: 10.1103/physrevd.90.013008
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of heavy sneutrinos in low-scale seesaw models

Abstract: There have been some recent claims in the literature about large right-handed sneutrinos contributions to lepton flavor violating observables like μ → 3e or μ − e conversion in nuclei in supersymmetric low-scale seesaw models. These large contributions originate from Z-penguin diagrams which show a much weaker dependence on the heavy masses than the photonic contributions. We have traced this to an error in the evaluation of the corresponding loop amplitudes which has propagated in the literature. We explicitl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
(143 reference statements)
1
10
0
Order By: Relevance
“…(5) and (3) is the constant The result of Ref. [4] has been confirmed by the authors of Refs. [2,3] in Ref.…”
Section: + Frprv Izrsupporting
confidence: 79%
“…(5) and (3) is the constant The result of Ref. [4] has been confirmed by the authors of Refs. [2,3] in Ref.…”
Section: + Frprv Izrsupporting
confidence: 79%
“…The supersymmetric contributions to boxes, Higgs penguins, photon penguins were found to perfectly agree with [78,103], while the supersymmetric Z-penguins only differ from [78] via a constant term as pointed out in [77]. This constant term does not impact the result of [78] where a high-scale seesaw mechanism is considered but it can lead to non-physical results in low-scale seesaw models.…”
Section: Jhep11(2014)048mentioning
confidence: 54%
“…Later, this result was (qualitatively) confirmed in [70] and further exploited in several phenomenological studies [73][74][75][76]. However, in [77] it was shown that the results in [72] (and the subsequent studies [73][74][75][76]) are incorrect, due to an inconsistency in [78]. While -3 -…”
Section: Introductionmentioning
confidence: 74%
“…[36]. We also note that the γ-and Z-penguin diagrams (including the supersymmetric counterparts) give vanishing contributions [36,[38][39][40][41][42]. The last term which is the new contribution in our analysis was not included in Ref.…”
Section: R-parity Violating Interactionsmentioning
confidence: 99%